KOMPETENCJE NAUCZYCIELA JĘZYKA OBCEGO W PRZEDSZKOLU IMMERSYJNYM. PRZYGOTOWANIE STUDENTÓW KIERUNKÓW NEOFILOLOGICZNYCH DO WYKONYWANIA ZAWODU NAUCZYCIELA W PRZEDSZKOLU DWUJĘZYCZNYM - Bielicka, Małgorzata (Neofilolog, 2019)
This paper attempts to describe the competences of the preschool teacher. Focus is placed on communicative competences both in the pedagogical dimension, as well as in the in L2. The next point of the paper is to address the following question: how are foreign language teacher trainees prepared for work as L2-teachers in immersive preschools? The conclusions are made on the basis of a 150-hour observation which was conducted in an immersive Polish-German preschool in Poznań.